The emerging role and clinicopathological significance of MFSD12 in cancer and lysosomal storage diseases - Liqiong Ding (Frontiers Media S.A., 2024)
MFSD12 protein has recently risen as a key factor in malignancy and plays a potential role in a variety of complex oncogenic signaling cascades. Current studies suggest that MFSD12 has a positive complex role in the growth and progression of tumors such as melanoma, breast cancer, and lung cancer. At the same time, as a transporter of cysteine, MFSD12 is also involved in the development of lysosomal storage diseases. Therefore, MFSD12 may be an effective target to inhibit tumor development, block metastasis, and expand the therapeutic effect. This article reviews the molecular mechanisms of MFSD12 in a variety of cancers and lysosomal storage diseases.